Scalability of Continuous Flow Production of Metal–Organic Frameworks. Issue 9 (14th April 2016) - Rubio‐Martinez, Marta; Hadley, Trevor D.; Batten, Michael P.; Constanti‐Carey, Keri; Barton, Tim; Marley, Dylan; Mönch, Andreas; Lim, Kok‐Seng; Hill, Matthew R.
Abstract: Achieving the large‐scale production of metal–organic frameworks (MOFs) is crucial for their utilization in applied settings. For many MOFs, quality suffers from large‐scale, batch reaction systems. We have developed continuous processes for their production which showed promise owing to their versatility and the high quality of the products. Here, we report the successful upscaling of this concept by more than two orders of magnitude to deliver unprecedented production rates and space‐time‐yields (STYs) while maintaining the product quality. Encouragingly, no change in the reaction parameters, obtained at small scale, was required. The production of aluminium fumarate was achieved at an STY of 97 159 kg m −3  day −1 and a rate of 5.6 kg h −1 . Abstract : Lab of plenty : The production of metal–organic frameworks (MOFs) on a large scale is crucial for their eventual application in industry. A continuous‐flow processes for MOF production is successfully scaled up, without any reoptimization of the synthesis, by more than two orders of magnitude to deliver unprecedented production rates (5.6 kg h −1 ) and space–time yields (97 159 kg m −3  day −1 ).